2009
DOI: 10.1192/bjp.bp.107.047498
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural impairments and genetic liability to familial bipolar I disorder

Abstract: Disturbed structural integrity within key intra- and interhemispheric tracts characterises both bipolar disorder and genetic liability for this illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
128
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(148 citation statements)
references
References 39 publications
14
128
2
3
Order By: Relevance
“…These regions recapitulate those reported to have reduced WM volume and density, and reductions in fractional anisotropy in prior studies of unaffected relatives of BD patients, 21,22,39,[49][50][51] in addition to those with established BD. 49,[52][53][54][55][56][57][58] The specific involvement of the IFG adds to a converging body of evidence from structural and functional studies of BD. [59][60][61][62][63][64] Likewise, the involvement of the insula adds to a growing number of reports of structural and functional differences in HR cohorts.…”
Section: Discussionmentioning
confidence: 53%
“…These regions recapitulate those reported to have reduced WM volume and density, and reductions in fractional anisotropy in prior studies of unaffected relatives of BD patients, 21,22,39,[49][50][51] in addition to those with established BD. 49,[52][53][54][55][56][57][58] The specific involvement of the IFG adds to a converging body of evidence from structural and functional studies of BD. [59][60][61][62][63][64] Likewise, the involvement of the insula adds to a growing number of reports of structural and functional differences in HR cohorts.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, all but one [180] tractography study showed reduced white matter integrity in the anterior thalamic radiation [181][182][183], which passes through the anterior limb of the internal capsule [184] in depressed, euthymic, and manic patients. In line, reduced white matter integrity in the anterior limb of the internal capsule has also been repeatedly observed in bipolar patients [173,185,186]. Similar, reduced integrity of the uncinate fasciculus, which interconnects the amygdala with the orbitofrontal cortex and the anterior cingulate cortex [187], has also been frequently observed in depressed and euthymic bipolar disorder patients [173,180,182,183,188,189].…”
Section: White Matter Alterationsmentioning
confidence: 49%
“…14,23,24,27 Indeed, low FA was found to correlate with genetic vulnerability to BD as well as with lipid peroxidation markers, suggesting the potential role of oxidative stress in altering white matter microstructure. 15,35 However, white matter findings remain inconsistent, suggesting that further studies are needed to validate its potential use as a biomarker for BD.…”
mentioning
confidence: 99%